Evaluating Non-Market Values of Agroecological and Socio-Cultural Benefits of Diversified Cropping Systems - Latvala, Terhi; Regina, Kristiina; Lehtonen, Heikki (Springer, 2021)
We explored how consumers value the ecological and socio-cultural benefits of diversified food production systems in Finland. We used a stated preference method and contingent valuation to quantify consumers’ willingness to pay (WTP) for the benefits of increased farm and regional scale diversity of cultivation practices and crop rotations. Three valuation scenarios were presented to a representative sample of consumers: the first one focused on agroecosystem services on cropland, the second on wider socio-cultural effects and the third was a combination of them. The results suggest that consumers are willing to pay on the average €228 per household annually for the suggested diversification. This is equal to €245 per hectare of cultivated cropland. The results also indicate that 21% of consumers were not willing to pay anything to support more diverse cropping systems. The relatively high WTP for both agroecological and socio-cultural benefits provide important messages for actors in the food chain and for policy makers on future targeting of economic resources within agri-environmental schemes.
Keywords: diverse farming system; agroecosystem services; sustainable agriculture; valuation